Coordination of Self- and Parental-Regulation Surrounding Type I Diabetes Management in Late Adolescence. Issue 1 (12th December 2017) - Butner, Jonathan E; Berg, Cynthia A; Munion, A K; Turner, Sara L; Hughes-Lansing, Amy; Winnick, Joel B; Wiebe, Deborah J
Abstract : Daily self-regulation of emotions, cognitions and behaviors to support diabetes occurs separate from daily regulation of parental involvement in late adolescence, but is better on days when mothers help. Abstract: Background: Type 1 diabetes management involves self- and social-regulation, with past research examining components through individual differences unable to capture daily processes. Purpose: Dynamical systems modeling was used to examine the coordinative structure of self- and social-regulation (operationalized as parental-regulation) related to daily diabetes management during late adolescence. Methods: Two hundred and thirty-six late adolescents with type 1 diabetes ( M age = 17.77 years, SD = .39) completed a 14-day diary reporting aspects of self- (e.g., adherence behaviors, cognitive self-regulation failures, and positive and negative affect) and parental-regulation (disclosure to parents, knowledge parents have, and help parents provide). Results: Self-regulation functioned as one coordinative structure that was separate from parental-regulation, where mothers and fathers were coordinated separately from each other. Mothers' perceived helpfulness served as a driver of returning adolescents back to homeostasis. Conclusions: The results illustrate a dynamic process whereby numerous facets of self- and social-regulation are coordinated in order to return diabetes management to a stable state.